Collectors of algae in Mexico (1787-1954) - Godínez Ortega, José Luis (Instituto de Ecología, A.C., 2008)
Biographical as well as bibliographical information is provided about the collectors of algae in Mexico during the period 1787-1954. The data were obtained by consulting domestic and foreign herbaria, direct communication with the curators, and revision of relevant literature. Information was found concerning 51 collectors, mainly of European and American origin; material collected by them was deposited in 16 herbaria: eight in Europe, seven in America and one in Australia. The work of collectors gathers information of the phyla: Cyanobacteria, Rhodophyta, Ochrophyta (including Phaeophyceae and Xanthophyceae), Bacillariophyta, Chlorophyta and Charophyta, the best represented being Bacillariophyta and Rhodophyta. Dates and locations of the regions surveyed in 26 states are included. In the period covered by the study about 477 new species were discovered.